PELAKSANAAN PENDAYAGUNAAN ZAKAT PRODUKTIF OLEH MUSTAHIK DI BAITULMAAL MUNZALAN INDONESIA CABANG KUBU RAYA - NIM. A1012201095, PADIA PAZIRA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac Baitulmaal Munzalan Indonesia is one of the Amil Zakat Institutions in Indonesia which has officially become LAZNAS (National Amil Zakat Institution) with the Decree of the Indonesian Ministry of Religion No. 693 of 2023. Zakat is a religious treasure that is believed to be able to overcome various social and economic problems. This research is to find out how the utilization of Productive Zakat by Mustahik in Baitulmaal Munzalan Indonesia Kubu Raya Branch. The methodology used in this research is Empirical Legal research. This type of field research through a descriptive approach that aims to provide an overview, explaining what is obtained from research collected through observation, documents, and interviews. Based on the results of research and discussion that the utilization of productive zakat by mustahik in Baitulmaal Munzalan Indonesia Kubu Raya Branch is not maximized. the utilization of zakat is carried out in stages, consumptive and productive in terms of spirituality / Tarbiyah. While the utilization of zakat in stages on independent mustahik has not been implemented due to two contributing factors, namely 1. the zakat manager lacks human resources (Human Resources) to survey the field and crosscheck the development of mustahik one by one in monitoring. Mustahik illiteracy and inconsistency of mustahik in following activities in the productive mustahik program. 2. Mustahik has their own obstacles such as taking care of children, a sick husband, working as odd jobs to meet basic needs and not being fluent in learning and understanding the Qur'an properly and correctly so that currently they have not passed the stages in the productive mustahik program. Keywords: Utilization, Productive Zakat, Mustahik, Muzakki Abstrak Baitulmaal Munzalan Indonesia adalah salah satu Lembaga Amil Zakat yang ada di Indonesia yang sudah resmi menjadi LAZNAS (Lembaga Amil Zakat Nasional) dengan SK Kemenag RI No. 693 Tahun 2023. Zakat merupakan harta ibadah yang diyakini mampu mengatasi berbagai permasalahan Sosial dan Ekonomi. Penelitian ini untuk mengetahui bagaimana pendayagunaan Zakat Produktif Oleh Mustahik di Baitulmaal Munzalan Indonesia Cabang Kubu Raya. Metodelogi yang digunakan dalam penelitian ini adalah penelitian Hukum Empiris. Jenis penelitian lapangaan melalui pendekatan deskriptif yang bertujuan memberikan Gambaran,menjelaskan apa adanya suatu yang diperoleh dari penelitian dikumpulkan melalui observasi, dokumen, dan wawancara. Berdasarkan hasil penelitian dan pembahasan Bahwa pendayagunaan zakat produktif oleh mustahik di Baitulmaal Munzalan Indonesia Cabang Kubu Raya dilaksanakan belum maksimal. pendayagunaan zakat dilakukan secara bertahap, konsumtif dan produktif dari sisi kerohanian/Tarbiyah. Sedangkan pendayagunaan zakat dalam tahapan pada mustahik mandiri belum dilaksanakan dikarenakan ada dua faktor penyebab yaitu 1. pengelola zakat kekurangan SDM (Sumber Daya Manusia) untuk survei di lapangan dan mengcroschek perkembangan mustahik satu persatu dalam monitoring. Mustahik buta aksara Dan ketidak konsistensi mustahik dalam mengukuti kegiatan pada program mustahik produkrif. 2. Mustahik memiliki kendala masing